New development: China's debt transparency and the case of urban construction investment bonds. Issue 3 (16th April 2017) - Bo, Lan; Mear, Fred C. J.; Huang, Jingchi
Abstract : China's true level of local government debt is unknown. The central government recently introduced policies to increase transparency and close some of the obscure financial instruments. Urban construction investment bonds (UCIBs) are one of the key instruments affected by these changes. Both positive and negative impacts can be expected. The issues the Chinese government is facing and its policy response provide important lessons for other governments.